Clinical decision-making in patients with non-ST-segment-elevation myocardial infarction: more than risk stratification - Xiang, Guangze; Cao, Gaoyang; Gao, Menghan; Hu, Tianli; He, Wujian; Gu, Chunxia; Hong, Xulin (Frontiers in Cardiovascular Medicine, 2024)
Objective This study aims to explore the association between risk stratification and total occlusion (TO) of the culprit artery and multivessel disease (MVD) in patients with non-ST-segment-elevation myocardial infarction (NSTEMI) and to obtain more data on clinical decision-making in addition to risk stratification. Methods We retrospectively collected data from 835 patients with NSTEMI admitted to our hospital between 1 January 2016 and 1 August 2022. All patients underwent percutaneous coronary intervention (PCI) within 72 h of admission. We excluded patients with a history of cardiac arrest, myocardial infarction, coronary artery bypass grafting, or PCI. Univariate and multivariate regression analyses were performed to determine the predictors of acute TO and MVD. Results A total of 349 (41.8%) patients presented with a TO culprit vessel, whereas 486 (58.2%) had a patent culprit vessel. Thrombolysis in myocardial infarction (TIMI) and Global Registry of Acute Coronary Events (GRACE) risk stratifications were similar between the two groups of patients (P = 0.712 and 0.991, respectively). The TO infarct vessel was more commonly observed in the left circumflex artery. Patients with TO were more likely to develop MVD (P = 0.004). Univariate and multivariate linear regression analyses were performed to evaluate the role of variables in the presence of TO and MVD in patients with NSTEMI. Regional wall motion abnormalities (RWMAs) [odds ratio (OR) = 4.022; confidence interval (CI): 2.782–5.813; P < 0.001] were significantly linked to TO after adjusting for potentially related variables. Furthermore, age (OR = 1.032; CI: 1.018–1.047; P < 0.001), hypertension (OR = 1.499; CI: 1.048–2.144; P = 0.027), and diabetes mellitus (OR = 3.007; CI: 1.764–5.125; P < 0.001) were independent predictors of MVD in patients with NSTEMI. TIMI and GRACE risk scores were related to MVD prevalence in the multivariate logistic regression model. Patients with a TO culprit vessel had a higher risk of out-of-hospital cardiac death after a 2-year follow-up compared with those without a TO culprit vessel (P = 0.022). Conclusion TIMI and GRACE risk scores were not associated with a TO of the culprit artery; however, they correlated with the prevalence of MVD in patients with NSTEMI. RWMA is an independent predictor of acute TO in patients with NSTEMI. Patients with a TO culprit vessel had worse clinical outcomes than those without a TO culprit vessel.